Analisis Strategi Pengembangan Objek Wisata Pemandian Peridon Siap Maju di Tinjau Dari Persfektif Bisnis Syariah (Study Kasus Pemandian Peridon Siap Maju di Kabupaten Pasaman Barat) - Putrianti, Welli; Sonita, Era (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This thesis is titled “Analysis of Development Strategy for Peridon Siap Maju Swimming Pool Tourist Attraction Viewed from the Perspective of Islamic Business”. The study aims to evaluate the development strategy of tourist attractions in Pasaman Barat Regency, focusing on Peridon Siap Maju Swimming Pool, established in 2019. This tourist attraction has great potential but has experienced a decline in visitor numbers in recent years. Through SWOT analysis, this study identifies the strengths, weaknesses, opportunities, and threats faced by the attraction. The results show that the natural beauty and unique facilities are the main strengths, while the lack of supporting facilities and accessibility issues are the weaknesses. Opportunities for development include sustainable tourism and ecotourism trends, while threats include the risk of environmental damage. This study also integrates Islamic principles into business development, such as providing halal food and separating facilities for men and women. Therefore, the proposed development strategy includes improving infrastructure, providing worship facilities, and more effective promotion to attract visitors. This research is expected to contribute to the development of sustainable local tourism that aligns with Islamic values, as well as improve the welfare of the local community through job creation and increased income.